EFFECTIVENESS OF ENVIRONMENTAL CRIMINAL LAW ENFORCEMENT IN CASES OF ENVIRONMENTAL CRIME OF ILLEGAL LOGGING CASE STUDY AT THE SUMATERA ELEPHANT FOUNDATION - Adillah Fajar Siddiq; Abdulrahman Nur Wahidin; Aulia Rahman Hakim Hasibuan (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Illegal logging is a significant environmental problem, especially in developing countries with large tropical forest areas. This activity not only causes forest degradation, but also has an impact on the loss of biodiversity, climate change, and socio-economic conflicts in local communities. This study aims to analyze the causal factors, impacts, and mitigation efforts of illegal logging. The results show that the main factors that trigger illegal logging include weak law enforcement, high demand for illegal wood, and economic pressure at the local level. The impacts include ecosystem damage, increased carbon emissions, and decreased quality of life for indigenous and local communities. To overcome this problem, effective strategies include increasing supervision, empowering local communities, implementing strict policies, and cooperation between countries in controlling the illegal wood trade. This study recommends a holistic approach involving various stakeholders to protect forests sustainably. The Sumatran Elephant Foundation has a very important role in overcoming this problem. As a conservation institution, Yagasu not only monitors and documents illegal logging activities, but is also active in conducting education and advocacy activities to the community about the importance of protecting mangrove forests and how to properly process mangrove products.